Thermal and Kinetic Study of Fine Coal And Palm Kernel Shell Gasification Using TGA Analysis - Hendra Dwipayana; Muhammad Faizal; Muhammad Said; Hasanudin Hasanudin (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2025)
Indonesia is rich in natural resources, including coal and palm kernel shells (PKS), which can be used in the gasification process. This study compares the gasification potential of palm kernel shells and fine coal, focusing on their thermal properties and activation energy. Thermogravimetric Analysis (TGA) shows that PKS have higher volatile matter (67.25%) and lower fixed carbon (20.90%) than fine coal (33.53% volatile matter, 32.98% fixed carbon). at 450 Â°C, PKS lose 11% of their mass in one hour and reach a 78% loss by the end of the process, while fine coal loses 70% after more than 200 minutes. The activation energy for PKS is lower (38.925 J/mol) than fine coal (41.012 J/mol). In gasification, palm kernel shells produce more hydrogen (26% mol) and less carbon dioxide (11% mol) than fine coal, which produces more methane (28% mol) and carbon dioxide (22% mol). These results suggest that PKS are a more efficient and eco-friendly option for gasification.Keywords: Fine coal, palm kernel shells, activation energy, thermogravimetric analysis (TGA), gasification